2017
DOI: 10.3390/ijms18051076
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Inhibits Periodontal Ligament Stem Cell Apoptosis under Excessive Oxidative Stress

Abstract: The present study aimed to analyze novel mechanisms underlying Nrf2-mediated anti-apoptosis in periodontal ligament stem cells (PDLSCs) in the periodontitis oxidative microenvironment. We created an oxidative stress model with H2O2-treated PDLSCs. We used real-time PCR, Western blotting, TUNEL staining, fluorogenic assay and transfer genetics to confirm the degree of oxidative stress and apoptosis as well as the function of nuclear factor-erythroid 2-related factor 2 (Nrf2). We demonstrated that with upregulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…Our results showed that Nrf2 over-expression effectively diminished TUNEL staining, reduced PARP cleavage and decreased the activation of Caspase-3, Caspase-8, and Caspase-9 in IL-1β-stimulated OA chondrocytes (Figure 5B, C and 6A). A recent report demonstrated that Nrf2 activation exerts anti-apoptotic effects by upregulating the levels of Bcl-2, in addition to downregulating Bax and c-fos expression in a different cell type [67]. In agreement with this study, we found that Nrf2 over-expression inhibited the expression of pro-apoptotic proteins Bax, Bad and Bid and upregulated the expression of anti-apoptotic proteins Bcl2, Bcl-xl and Mcl-1 in IL-1β-stimulated human OA chondrocytes (Supplementary Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Nrf2 over-expression effectively diminished TUNEL staining, reduced PARP cleavage and decreased the activation of Caspase-3, Caspase-8, and Caspase-9 in IL-1β-stimulated OA chondrocytes (Figure 5B, C and 6A). A recent report demonstrated that Nrf2 activation exerts anti-apoptotic effects by upregulating the levels of Bcl-2, in addition to downregulating Bax and c-fos expression in a different cell type [67]. In agreement with this study, we found that Nrf2 over-expression inhibited the expression of pro-apoptotic proteins Bax, Bad and Bid and upregulated the expression of anti-apoptotic proteins Bcl2, Bcl-xl and Mcl-1 in IL-1β-stimulated human OA chondrocytes (Supplementary Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of Nrf2 and subsequent inhibition of antioxidant production have been associated with more advanced periodontitis [7]. In addition, Nrf2 overexpression has been proved to activate antioxidative enzymes and thus effectively inhibit periodontal ligament stem cell apoptosis in the local oxidative stress microenvironment of periodontitis [8]. Moreover, Nrf2 also plays important roles in DM-related diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…During the manual search, no additional articles were selected. Eight articles were excluded after full-text reading: six articles did not directly compare microbiological data from healthy teeth with healthy implants, or periodontitis and peri-implantitis 5,7,9,13,14,15,16 and two studies did not present statistical analysis comparing periodontal and peri-implant health or disease (Table 2). 17,18 Therefore, 8 articles were included in the current systematic review.…”
Section: Studies Includedmentioning
confidence: 99%